The Effectiveness of Flipped Classrooms in Distance Education During the Covid-19 Pandemic - Villarica, Mia Villar (International Journal of Computing Sciences Research, 2023)
Purpose - COVID-19 brought a significant impact on Philippine Higher Education Institutions, the majority of the HEIs were compelled to switch over to remote education. This study aims to investigate the effectiveness of flipped classroom instruction in remote education. Method - The study utilized two sets of validated questionnaires which contained numerical survey and open-ended survey responses adopting mixed-method from 122 students out of 166 who completed a course in a flipped classroom in a remote learning environment for a semester. The quantitative responses were analyzed using descriptive statistics and the qualitative responses was examined using a qualitative data analysis software. Results - The research revealed that clear instructional design and distinct pedagogical strategies are substantial in online flipped classroom instruction. It also revealed that students believed that it improved their learning performance, provided flexible learning, and fostered high self-efficacy, which gathered a significant level of agreement. In addition, the study shows that the implications of creating video lectures have been beneficial during asynchronous and synchronous interactions. On the other hand, significant challenges, such as Internet accessibility and digital resources, a heavy reliance on student motivation, and the promotion of a careless learning environment were revealed. Conclusion - The research revealed that students are generally satisfied with flipped classes in distant environments and student learning improved because of easy access to resources for self-paced learning. Recommendations – Flip classroom instruction is an effective pedagogical approach in remote learning environments from a group to an individual learning space. A significant level of instructor involvement is required in course planning, preparation, and classroom management. It is significant to maintain constant communication with the students and keep track of their progress and prevent a careless learning environment. Research Implications – Due to the Covid-19 pandemic, there was a significant shift towards digitalization, including the realm of education. Online classes and distance learning ceased to be mere trends and became a reality that everyone had to adapt to. However, the pandemic highlighted a deeper need beyond the use of technological devices. It underscored the importance of nurturing individuals who are emotionally intelligent and capable of leveraging digital transformation as a means for social transformation.